"Plasma Cell Hepatitis" in Liver Allografts: Identification and Characterization of an IgG4‐Rich Cohort. Issue 11 (6th September 2013) - Castillo‐Rama, M.; Sebagh, M.; Sasatomi, E.; Randhawa, P.; Isse, K.; Salgarkar, A. D.; Ruppert, K.; Humar, A.; Demetris, A. J.
Abstract: Plasma cell hepatitis (PCH), also known as " de novo autoimmune" hepatitis, is an increasingly recognized, but suboptimally named and poorly understood, category of late allograft dysfunction strongly resembling autoimmune hepatitis (AIH): They share plasma‐cell‐rich necro‐inflammatory activity on biopsy, autoantibodies and steroid responsiveness, but overlap with rejection is problematic. A retrospective study of clinical, serological, histopathological and IgG4 immunohistological features of PCH (n = 20) in liver allograft recipients, native liver AIH (n = 19) and plasma‐cell‐rich renal allograft rejection (n = 20) showed: (1) high frequency (44%) of HLA‐DR15; (2) less female predominance (p = 0.03) and (3) n = 9/20 PCH recipients showed >25 IgG4+ plasma cells/high‐power field (IgG4+ PCH) versus AIH (n = 1/19, p = 0.008) or plasma‐cell‐rich kidney rejection (n = 2/20, p = 0.03). The IgG4+ PCH (n = 9) subgroup showed lower alanine transaminase (ALT) (p < 0.01) and aspartate transaminase (AST) (p < 0.05) at index biopsy but (a) higher plasma cell number/percentage, (b) more aggressive‐appearing portal/periportal and perivenular necro‐inflammatory activity and (c) more severe portal/periportal fibrosis than IgG4− PCH (n = 11). Significant demographic, histopathologic and plasma cell phenotype differences between PCH and AIH suggest distinct pathogenic mechanisms for at least the IgG4+ PCH subgroup likely representing an overlap between allo‐ and auto‐immunity. IgG4+ PCH was associated with fibrosis, but also highly responsive to increased immunosuppression. Abstract : An IgG4‐rich cohort of patients with plasma cell hepatitis after liver transplantation shows demographical, histopathological and plasma cell phenotype features distinct from autoimmune hepatitis in native livers, suggesting distinct pathophysiological disease mechanisms likely representing an overlap between allo‐ and autoimmunity. See editorial by Manns and Mix on page 2792.